Revising the diagnosis of congenital amusia with the Montreal Battery of Evaluation of Amusia - Pfeifer, Jasmin; Hamann, Silke (Frontiers in Human Neuroscience, 2015)
This article presents a critical survey of the prevalent usage of the Montreal Battery of Evaluation of Amusia (MBEA; Peretz et al., 2003) to assess congenital amusia, a neuro-developmental disorder that has been claimed to be present in 4% of the population (Kalmus and Fry, 1980). It reviews and discusses the current usage of the MBEA in relation to cut-off scores, number of used subtests, manner of testing, and employed statistics, as these vary in the literature. Furthermore, data are presented from a large-scale experiment with 228 German undergraduate students who were assessed with the MBEA and a comprehensive questionnaire. This experiment tested the difference between scores that were obtained in a web-based study (at participants’ homes) and those obtained under laboratory conditions with a computerized version of the MBEA. In addition to traditional statistical procedures, the data were evaluated using Signal Detection Theory (SDT; Green and Swets, 1966), taking into consideration the individual’s ability to discriminate and their response bias. Results show that using SDT for scoring instead of proportion correct offers a bias-free and normally distributed measure of discrimination ability. In addition it is also demonstrated that a diagnosis based on an average score leads to cases of misdiagnosis. The prevalence of congenital amusia is shown to depend highly on the statistical criterion that is applied as cut-off score and on the number of subtests that is considered for the diagnosis. In addition, three different subtypes of amusics were found in our sample. Lastly, significant differences between the web-based and the laboratory group were found, giving rise to questions about the validity of web-based experimentation.